SPECTRUM OF PULMONARY EXACERBATION IN CHILDREN AND ADOLESCENT WITH CYSTIC FIBROSIS AND PHYSICIANS’ PRACTICES: EXPERIENCE FROM TERTIARY CARE CENTER FROM LOWER-MIDDLE INCOME COUNTRY - Abdul Aziz, Danish; Shahid, Shahira; Alam, Anusha; Aziz, Namrah; Iftikhar, Haissan; Mir, Fatima (Journal of Ayub Medical College Abbottabad, 2021)
Background: Pulmonary exacerbations (PEx) are major contributor of significant morbidity and mortality in CF patients. Managing PEx needs standardization and without standard local practice guidelines there will be significant variation in practice in managing these children. The aim of this study is to analyse the clinical management of PEx in our setup and to document variation in practices among physicians. Methods: Children and adolescents ‰¤18 years with CF pulmonary exacerbations admitted at high dependency unit (HDU) or wards were included in the study. Frequency of different intravenous antibiotic combinations were documented along with use of different inhaled antibiotics and inhalation therapy. Practices of different physician were further studied with regards to use of systemic steroids, oral azithromycin and inhaled antibiotics. One way ANOVA was used to assess differences between physicians’ practices. Results: Fifty-seven patients were selected according to the inclusion criteria for 114 different exacerbations. Mean pulmonary exacerbation (PEx) for a patient (events/person-year) over five years were 3.16±1.41 per year and average length of stay was 5.7±4.4 days. Combination of intravenous ceftazidime and amikacin was the most frequently used regimen (28.07%). Five different physicians dealing with majority of the exacerbations (n=74) were studied further. Variability among consultants was significant in using systemic steroids (21.42-92.30%), use of maintenance oral azithromycin (0-80%) and inhaled antibiotics (0-86.6%). Conclusion: Significant variation exists in practices of physicians dealing with CF PEx. Variability observed in our study will definitely provide openings for local CF experts to come up with standardized inpatient exacerbation guidelines.